Electrochemical and chemical dealloying of nanoporous anode materials for energy storage applications - Muhammad Afiq Irfan Mohd Shumiri; Abdillah Sani Mohd Najib; Andi Erwin Eka Putra; Nor Akmal Fadil (Science and Technology of Advanced Materials)
Traditionally employed in alloy corrosion studies, dealloying has evolved into a versatile technique for fabricating advanced porous materials. The unique architecture of interconnected pore channels and continuous metal ligaments endows dealloyed materials with high surface-to-volume ratio, excellent electron conductivity, efficient mass transport and remarkable catalytic activity, positioning them at the forefront of nanomaterial applications with significant potential. However, reproducible synthesis of these structures remains challenging due to limitations in conventional dealloying techniques. Herein, this review attempts to consolidate recent progress in electrochemical and chemical dealloying methods for nanoporous anodes in energy storage and conversion applications. We begin by elucidating the fundamental mechanisms driving dealloying and evaluate key factors influencing dealloying conditions. Through a review of current research, we identify critical properties of dealloyed nanoporous anodes that warrant further investigation. Applications of these materials as anodes in metal-ion batteries, supercapacitors, water splitting and photocatalyst are discussed. Lastly, we address ongoing challenges in this field and propose perspectives on promising research directions. This review aims to inspire new pathways and foster the development of efficient dealloyed porous anodes for sustainable energy technologies.